2023
DOI: 10.31083/j.jin2206149
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Model of Ligusticum Chuanxiong Hort. Against Cerebral Stroke Using Network Pharmacology and Transcriptomics Analyses

Jinfeng Zhang,
Chongyin Cai,
Ying Luo
et al.

Abstract: Background: Cerebral stroke is a leading cause of death and disability worldwide. Ligusticum Chuanxiong Hort. (LCH), a well-known Chinese herb, is widely used for the treatment of cerebral stroke. This study aimed to investigate the underlying mechanisms of LCH in cerebral stroke and develop a diagnostic model. Methods: We employed network pharmacology analyses to identify the active compounds, targets, and underlying mechanisms of LCH for treating cerebral stroke. Molecular docking was performed to visualize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…According to traditional Chinese medicine, CIS is attributed to wind, fire, phlegm, blood stasis, and deficiency, with L. striatum DC to improve clinical symptoms of CIS by enhancing qi and blood circulation, activating blood flow, and resolving blood stasis. Modern scientific studies have shown that L. striatum DC can be effective in stroke treatment, with its mechanism of action linked to the regulation of the TNF/IL-17 signaling pathway ( Zhang et al, 2023 ). Ligustrazine, an active compound in L. striatum DC , plays a key role in these therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%
“…According to traditional Chinese medicine, CIS is attributed to wind, fire, phlegm, blood stasis, and deficiency, with L. striatum DC to improve clinical symptoms of CIS by enhancing qi and blood circulation, activating blood flow, and resolving blood stasis. Modern scientific studies have shown that L. striatum DC can be effective in stroke treatment, with its mechanism of action linked to the regulation of the TNF/IL-17 signaling pathway ( Zhang et al, 2023 ). Ligustrazine, an active compound in L. striatum DC , plays a key role in these therapeutic effects.…”
Section: Introductionmentioning
confidence: 99%